Pulmonary tuberculosis patients with diabetes mellitus have a more severe degree of chest X-ray compared to pulmonary tuberculosis patients without diabetes mellitus - Ramzi, Muhammad; Putra, Muslim Andala; Subkhan, Mohammad (Gaceta Médica de Caracas, 2021)
Introduction: Pulmonary tuberculosis (TB) cases increase along with the increase in diabetes mellitus (DM) cases. The purpose of this study is to compare the description of Thorax X-ray severity between pulmonary TB patients without DM and pulmonary TB patients with DM.